Answer: B = –3a^2 + 11a + 5
For difference, the answer is
-3a^2 -5a -5
Explanation:
(3a – 3a^2) + (5 + 8a)
To find the sum or difference, we will open the brackets.
To look for l the sum, we add
3a – 3a^2 + 5 + 8a
Collecting like terms,
= -3a^2 +8a + 3a +5
= -3a^2 + 11a + 5
Option B is the right answer.
To look for the difference, we subtract.
(3a – 3a^2) - (5 + 8a)
Opening the brackets
3a – 3a^2 - 5 - 8a
Collecting like terms
-3a^2 + 3a -8a -5
= -3a^2 -5a -5
The options available corresponds only to what we got for the sum, so
-3a^2 + 11a + 5 is the answer